The Implementation of Character Education in the Civics Education Syllabus at SMA Negeri 1 Sleman - T Heru Nurgiansah; Jagad Aditya Dewantara; Fazli Rachman (Universitas of Muhammadiyah Makassar, 2020)
Abstract. Students ' behaviour lately is becoming more concerned with being far from virtue values, needing to improve students ' character to be better. This research aims to know: 1) The values of the character in the syllabus, 2) Implementation of character education in the PKn-bus, and 3) supporting factors and inhibiting the implementation of character education in PKn syllabus in SMA Negeri 1 Sleman. This research uses qualitative methods. Data retrieval is done with observation and interviews. PKn teacher at SMA Negeri 1 Sleman implements character education in PKn syllabus in the sidelines of the subject matter, provide for example, and habituation. The implementation of character education in syllabus is quite effective in forming students ' character, indicated by good student behavior during school. The contributing factor to the implementation of character education in syllabus is the teacher's cooperation in character education, support of the headmaster by providing literature, direction and coaching, as well as the instruction of 18 character values that must be applied. The factor is that when there is solid material, the teacher sometimes forgot and did not get to instill the character values related to the material. Teachers need to plan learning better, so that the subject matter can be completed and character planting is also possible.Keywords: Character Education, Citizenship Education.Abstrak. Perilaku siswa akhir-akhir ini semakin memprihatinkan yang jauh dari nilai-nilai kebajikan, perlu perbaikan karakter siswa agar menjadi lebih baik. Penelitian ini bertujuan untuk mengetahui : 1) nilai-nilai karakter yang ada dalam silabus PKn, 2) implementasi pendidikan karakter dalam silabus PKn, dan 3) faktor pendukung dan penghambat implementasi pendidikan karakter dalam silabus PKn di SMA Negeri 1 Sleman. Penelitian ini menggunakan metode kualitatif. Pengambilan data dilakukan dengan observasi dan wawancara. Guru PKn di SMA Negeri 1 Sleman mengimplementasikan pendidikan karakter dalam silabus PKn di sela menerangkan materi pelajaran, memberikan keteladanan, dan pembiasaan-pembiasaan. Implementasi pendidikan karakter dalam silabus cukup efektif membentuk karakter siswa, diindikasikan dengan perilaku siswa yang baik selama di sekolah. Faktor pendukung implementasi pendidikan karakter dalam silabus adalah kerja sama guru dalam pendidikan karakter, dukungan kepala sekolah dengan menyediakan literatur, arahan dan pembinaan, serta adanya petunjuk 18 nilai karakter yang harus diterapkan. Faktor penghambatnya adalah apabila terdapat materi yang padat, sehingga guru terkadang terlupa dan tidak sempat menanamkan nilai-nilai karakter yang berkaitan dengan materi tersebut. Guru perlu merencanakan pembelajaran secara lebih baik, sehingga materi pelajaran dapat diselesaikan dan penanaman karakter juga dapat dilakukan.Kata Kunci: Pendidikan Karakter; Pendidikan Kewarganegaraan